(Re)making the margins: Frontier assemblages and brokerage in Hambantota, Sri Lanka. (25th March 2022) - Goodhand, Jonathan; Walton, Oliver
Abstract: This article examines the dynamics of brokerage surrounding two moments of rupture (the tsunami and the end of the war) in Hambantota, a district in southern Sri Lanka and a key site of frontier development. We contrast the two development assemblages that emerged from these moments, examining how structural transformations shape the dynamics of brokerage, and how brokers mediate the effects of these transformations. By tracing the shifting fortunes of a local government broker, we reveal the changing power dynamics within these two assemblages, whilst highlighting how moments of rupture both open and shut down brokerage spaces.